The needs and experiences of women in sexually integrated prisons - Mahan, Sue (American journal of criminal justice, 1989)
Three issues were considered in this evaluation of the usefulness of co-corrections: violence, over-management and policies about sexuality. A study of one sexually integrated prison showed that co-corrections has both advantages and disadvantages for women. Inmates and staff were included in the research. Survey and anecdotal data were collected. The strengths of co-corrections were described from the data along with some suggestions for overcoming the weaknesses.